One-pot fructose conversion into 5-ethoxymethylfurfural using a sulfonated hydrophobic mesoporous organic polymer as a highly active and stable heterogeneous catalyst. Issue 17 (27th July 2021) - Manjunathan, Pandian; Upare, Pravin P.; Lee, Maeum; Hwang, Dong Won
Abstract : We report a sulfonated hydrophobic mesoporous organic polymer (MOP-SO3 H) as a highly efficient heterogeneous catalyst for one-pot 5-ethoxymethylfurfural (EMF) production from fructose in ethanol solvent. Abstract : We report a sulfonated hydrophobic mesoporous organic polymer (MOP-SO3 H) as a highly efficient heterogeneous catalyst for one-pot 5-ethoxymethylfurfural (EMF) production from fructose in ethanol solvent. MOP-SO3 H was fabricated by co-polymerization of divinylbenzene (DVB) and sodium p -styrene sulfonate (SPSS) followed by ion exchange with dilute H2 SO4, and its pore structure and acid density could be tuned easily by varying the mole ratio of SPSS to DVB. 31 P MAS NMR analysis using trimethylphosphine oxide as a base probe molecule indicated that MOP-SO3 H possessed a weaker Brønsted acid site than conventional cation-exchange resins. The superhydrophobic properties of MOP-SO3 H were retained even after incorporating a greater number of sulfonic acid groups into the polymer framework, while conventional solid acid resins exhibited hydrophilic properties. MOP-SO3 H exhibited a superior catalytic performance in comparison with conventional acid resins, a mesoporous acid catalyst, and homogeneous acid catalysts in EMF production from fructose. After optimization of various reaction conditions using MOP-SO3 H, a high EMF yield of 72.2% at 99.3% fructose conversion was achieved at 100 °C in a very short reaction time of 5 h. Notably, MOP-SO3 H showed a much higher EMF formation rate than the Amberlyst-15 catalyst (53.5 vs. 6.1 μmol g −1 min −1 ). This superior performance of the MOP-SO3 H catalyst was attributed to its unique feature of large surface area containing a large quantity of readily accessible acid sites distributed throughout the hydrophobic polymer framework. In addition to its high catalytic activity, the notable stability of the MOP-SO3 H catalyst was also confirmed by leaching and recyclability tests. Thus, owing to its excellent catalytic performance and easy scalability, MOP-SO3 H can potentially be used as an industrial heterogeneous catalyst to produce EMF from various fructose-containing biomass.